A review and reconstruction of the evaluation index system for high-quality development of urban agglomerations - Hongyu, Zhi; Arip, Mohammad Affendy Bin (Edelweiss Applied Science and Technology, 2025)
Since 2010, research literature on the evaluation of high-quality development in urban agglomerations has been analyzed by sorting and examining publication time, sources, indicator composition, research areas, methods, and data sources. This review summarizes academic achievements and identifies existing problems in this field. Based on this analysis, a new indicator system for the healthy development of Chinese urban agglomerations has been developed, incorporating both quantitative and qualitative perspectives. The goal is to provide a scientific and comprehensive evaluation framework for the sustainable development of Chinese urban agglomerations.